O desenvolvimento tecnológico da indústria naval de defesa: uma questão de estratégia - Coelho, Hélio Guilherme José (2009)
The conviction that there is a strong dependence on foreign technology in the shipping industry is result of a perception uncomfortable, acquired by work experience in Navy Brazil (MB), experiencing many difficulties, such as the high costs of items parts, as well as their availability sometimes scarce or non-existent for Construction and maintenance of operating means. This resulted in a reflection about the origin of these difficulties since factors such as the need to import the items, were very frequent and always subject to the imposition of deadlines excessively dilated to meet the operational needs, whatever the reasons which were alleged